PERMASALAHAN DALAM PENYELESAIAN SENGKETA KONSUMEN DI BPSK - Edwin Yuliska (Normative Jurnal Ilmiah Hukum, 2018)
Consumer protection is an interesting problem and is of concern to the Indonesian Government. This can be seen from the laws and regulations that regulate this matter, namely Law Number 8 of 1999 concerning Consumer Protection. Consumer protection is a very necessary thing to do because it is related to efforts to prosper society in relation to the growing development of trade transactions in the modern era. The Consumer Dispute Settlement Agency (BPSK) is expected to answer the demands of the community so that the litigation process runs fast, simple and cheap without any problems.